You need to use the following half angle identity, such that:

`cos^2(x/2) = (1 + cos x)/2`

Replacing `(1 + cos x)/2` for the term of equation `cos^2(x/2)` , yields:

`sin x + 2*(1 + cos x)/2 = 1`

Reducing duplicate factors, yields:

`sin x + 1 + cos x = 1`

`sin x + cos x + 1 - 1 = 0 `

`sin x + cos x = 0`

You may divide by `cos x` both sides, such that:

`sin x/cos x + 1 = 0`

Using the trigonometric identity `sin x/cos x = tan x` , yields:

`tan x + 1 = 0`

`tan x = -1 => x = tan^(-1) (-1) + k*pi`

`x = -pi/4 + k*pi`

**Hence, checking if the given equation has solutions, the answer is affirmative and the general solution to the equation is `x = -pi/4 + k*pi.` **

**Further Reading**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now